Utilization of mistletoe for the synthesis of copper nanoparticles and its clinical applications - Coteli, Ebru (European Journal of Chemistry, 2025)
Nanoparticles are substances with dimensions smaller than 100 nm. Nowadays, nanoparticles can be synthesized by many methods. Copper nanoparticles (CuNPs) were made using the green synthesis approach, using aqueous extracts of the pine mistletoe plant (Viscum album ssp. austriacum) and CuSO₄ metal salt. The formation of CuNPs was determined both by observing the color change and by the UV-vis method. Especially peaks were observed around the leaf (567 nm), fruit (560 nm), and branch (565 nm). Specific functional groups involved in the formation of CuNPs and the reduction of Cu0 were determined by FT-IR spectroscopy. In addition, SEM and EDS analyses of the synthesized CuNPs show that they are nanosized and their average size is less than 100 nm. In particular, it was determined that the size of fruit-derived CuNPs was the smallest (between 23.21 and 54.63 nm), and all synthesized CuNPs were spherical in shape. In addition, the antioxidant capacities of these plant extracts and CuNPs synthesized from them were investigated. For this purpose, DPPH• and ABTS•+ radical scavenging activities of the samples were determined. The DPPH• radical IC50 value of CuNPs obtained from the aqueous extract of fruit was determined as 151.41 µg/mL, and the ABTS•+ radical IC50 value was 160.43 µg/mL. The antioxidant results were compared with the standard ascorbic acid results. Furthermore, copper nanoparticles obtained from fruit extract were found to have the highest antioxidant activity. Furthermore, the antimicrobial activities of all samples were examined. In particular, the antiquorum activity of CuNPs synthesized from plant parts of V. album was determined for the first time. As a result, it was determined that the copper nanoparticles obtained from these plant parts had superior antioxidant and antimicrobial properties.